2020
DOI: 10.1038/s41598-020-63138-w
|View full text |Cite
|
Sign up to set email alerts
|

Corded Ware cultural complexity uncovered using genomic and isotopic analysis from south-eastern Poland

Abstract: During the Final Eneolithic the Corded Ware Complex (CWC) emerges, chiefly identified by its specific burial rites. This complex spanned most of central Europe and exhibits demographic and cultural associations to the Yamnaya culture. To study the genetic structure and kin relations in CWC communities, we sequenced the genomes of 19 individuals located in the heartland of the CWC complex region, southeastern Poland. Whole genome sequence and strontium isotope data allowed us to investigate genetic ancestry, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 66 publications
(116 reference statements)
5
20
0
1
Order By: Relevance
“…Furthermore, we confirmed the presence of sex-biased admixture previously seen in CWC individuals from Estonia, Poland, and Germany ( 27 , 38 , 39 ) in the Fatyanovo. To that end, we first compared autosomal and chrX outgroup f 3 results (fig.…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, we confirmed the presence of sex-biased admixture previously seen in CWC individuals from Estonia, Poland, and Germany ( 27 , 38 , 39 ) in the Fatyanovo. To that end, we first compared autosomal and chrX outgroup f 3 results (fig.…”
Section: Resultssupporting
confidence: 89%
“…2D). Furthermore, we confirmed the presence of sex-biased admixture previously seen in CWC individuals from Estonia, Poland and Germany 40,41,32,42,43 in the Fatyanovo ( Supplementary Fig. 3D).…”
Section: Early Farmer Ancestry In Fatyanovo Culture Individualssupporting
confidence: 89%
“…Haak et al (2015) also observed that the T allele increased in frequency only after the Yamnaya Steppe ancestry became ubiquitous in Central and Western Europe. Consistent with these findings, it was recently identified that the T allele is possessed by only one CWC individual from Sweden (Malmström et al, 2019), only one Final Neolithic individual from Switzerland (Furtwängler et al, 2020), and none of 16 CWC individuals from Poland (Witas et al, 2012;Linderholm et al, 2020), to mention a few. Using 230 ancient Eurasians, Mathieson et al (2015) found that the earliest appearance of the T allele is in a Central European Bell Beaker sample dated to between 2450 and 2140 BC, and the selective sweep dated to the last 4000 years (Burger et al, 2007;Gamba et al, 2014;Haber et al, 2016 for a review).…”
Section: Discussionmentioning
confidence: 67%